The Instructional Media Development of Digital Pop-Up Book PowerPoint in Islamic Religion Education and Character Subject at The Vocational High School - Dwi Puspitarini; Gita Magfiroh (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2025)
Pop-Up Book Digital is an electronic learning media developed from PowerPoint software. Pop-Up Book Digital is modeled into a digital media that when operated displays a 3-dimensional structure resembling a book. The digital Pop-Up Book PowerPoint media model is developed to address the low interest in learning and student interaction in Islamic Education (PAI) due to less engaging media. This product is also in line with the vision and mission of SMK 2 Pancasila Jember, which emphasizes character building, especially the value of tolerance, and supports teachers in presenting relevant learning media in the digital era.. Based on the results of the validation test and response test, this Pop-Up Book Digital product was declared very interesting, very practical and suitable for use as a learning medium. In this study, researchers developed a PowerPoint learning media product using the Pop-Up Book Digital model for Islamic Religious Education and Ethics subjects for class XI of SMK Negeri 2 Pancasila Jember. The type of research used is research and development (R&D) with the Planning, Production, Evaluation (PPE) stages developed by Richey and Klein. The validity test was carried out by three expert validators, namely, one expert validator for learning media and two expert validators for material. The product response test was carried out on PAI teachers and class XII Marketing students in 2024-2025. The results of the teacher response test obtained a score of 98%, while the small-scale student response test and the large-scale student response test obtained average scores of 86.60%, all categorized as "Very Good." The results of the expert validation test yielded an average score of 96.80%, both categorized as "Very Valid." Keywords: Digital Pop-Up Book, Islamic Education, Instructional Media Development